O São Francisco, um rio de muitas esperas - Laurent Vidal (Confins)
From the standpoint of "social history of waiting" this article pretends to propose another way to write the history of the São Francisco River. On one side, the São Francisco is the result of many hopes (geopolitical and social) that have left traces in the imagination - both public authorities and local populations. However « hope » is not the only possible definition of « waiting », which also means pause, stop. Moreover, from this point of view, we must note that the landscape of São Francisco river is marked by breaks of people on the move who, going upriver, have been the origin of the first urban cores and, more recently, of migrant camps.